Early postnatal growth failure in preterm infants is not inevitable. Issue 3 (22nd August 2018) - Andrews, Edward Thomas; Ashton, James John; Pearson, Freya; Beattie, R Mark; Johnson, Mark John
Abstract : Background: Previously published data have demonstrated that preterm infants experience a fall across marked centile lines for weight in early life with early poor head growth also reported. This study describes a single neonatal unit's experience of longitudinal change in weight, head circumference (HC) and length in a cohort of preterm infants born <32 weeks' gestation. Methods: Data were collected from a single neonatal unit between July 2012 and June 2017. This period followed the introduction of improved nutritional guidelines. Patients were grouped according to their gestational age at birth. Growth lines were constructed for weight, HC and length in each gestational age group from the median measures and compared with reference centile lines. Results: Data were analysed from 396 patients consisting of 2808, 1991 and 2004 measures for weight, HC and length, respectively. Longitudinal growth plots did not show an initial absolute weight loss in any of the subgroups. Across all groups, the mean change in SD score between birth and 36 weeks was −0.27 (95% CI −0.39 to −0.15). Conclusions: This description of longitudinal growth in a cohort of preterm infants demonstrates that early postnatal growth failure is not inevitable, with most infants growing along a trajectory close to their birth centile. There is no evidence of a 2 marked centile line weight decrease or weight loss. These data provide evidence to suggest that extrauterine weight gain tracking centile lines can be achieved.